Factors related to the cognitive appraisal of workplace health and safety change : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Hurley, Matt Raymond (Massey University, 2019)
Health and safety change is a critical and ongoing factor in New Zealand workplaces today, aiming to contribute to the enhanced health and safety performance of both organisations and society. There is a gap in the literature surrounding how and what factors relate to individual's responses to specific organisational change, such as safety-oriented change; the majority of literature focuses on restructuring and predominantly negatively experienced changes (Biggane, Allen, Amis, Fugate, & Steinbauer, 2017). We utilise the theory of cognitive appraisal (Lazarus & Folkman, 1984) integrated with a job demands and resources approach (Demerouti, Bakker, Nachreiner, & Schaufeli, 2001; Hobfoll, 1989) to explain why certain factors, such as Safety Climate, Role type, Perceived Scale of change, and Perceived Favourableness of change may relate to how individuals cognitively appraise change. Through the participation of 178 employees of various New Zealand organisations, within a multitude of industries and occupations, measures targeting the Perceived Scale at the personal and work unit level and Perceived Favourableness of change outcomes experienced, alongside measures of safety climate, challenge appraisal and threat appraisal with a number of demographic questions were distributed. Results demonstrated that Perceived Favourableness of change outcomes and Perceived Personal Scale of change played a key role in the appraisal process acting as situational factors predicting appraisal and emphasising the relevance of resource gain and its extrinsic and intrinsic value in change. Safety climate was found to not mediate responses to health and safety change, such as cognitive appraisal. Role type did not moderate appraisal. Findings indicated that organisations do not need to focus on developing a safety climate before implementing safety change and need to focus on perceptions of the scale and the favourable nature of change, utilising participation and involvement to achieve both desirable and functional change, and positive responses to the changes.
Keywords: Industrial hygiene; Industrial safety; New Zealand; Psychological aspects; Organizational change; Psychology, Industrial